Evaluation of phytochemical parameters, antibacterial and antihelminthic activity of leaves and bark extracts of plant Bombax ceiba - Shah, Suyogya; Ghimire, Kamana; Gupta, Amit Kumar; Pokhrel, Priyanka; Banerjee, Janmonjoy; Khanal, Hemanta; Pradhananga, Mahalaxmi (Journal of Applied Pharmaceutical Research, 2017)
Bombax ceiba, commonly known as the red silk-cotton tree, is a large, briefly deciduous tree occurring in warm monsoon forests in southern Asia. Various phytochemical constituents present in different plant parts has been already reported earlier to possess many biological activities, here in this work extraction was performed by mixture of solvent (distilled water: ethanol) as well as the individual solvents (water) and (ethanol). The phytochemical screening of the leaves and barks was found to exhibit the presence of carbohydrates, glycoside, saponin, phytosterol phenol, tannins, flavonoid, proteins and diterpenes and negative result for alkaloids in all the solvent extracts. The ethanolic extract of leaves was subjected to antihelmenthic activity and the result was found to be moderate.